2005
DOI: 10.1002/mrd.20122
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of hepatic IGF-I and IGF-II gene expression in the Marine TeleostSparus aurata

Abstract: The present work aimed to determine whether GnRH potentiates the effect of growth hormone (GH) on insulin-like growth factors (IGF-I and IGF-II) hepatic gene expression in Sparus aurata liver. Since several hepatic genes were shown to underlie direct regulation via the hepatic estrogen receptor, another aim was to extend our understanding of direct estrogen effects on liver IGFs gene expression. Pre-reproductive sea bream females were treated with GH, GnRH, estradiol-17beta, GH plus GnRH, and estradiol-17beta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 56 publications
4
28
0
Order By: Relevance
“…In the present study, the expression of both sbGHR1 and sbGHR2 was found to be decreased by estradiol treatment in black seabream. This decreased receptor expression in the seabream liver by estradiol in fact provides an explanation to a recent report that estradiol decreases GH-stimulated expression of IGF-I mRNA in the seabream liver (Carnevali et al 2005). In mammals, rather diverse observations on estradiol regulated GHR expression have been reported.…”
Section: Discussionmentioning
confidence: 57%
“…In the present study, the expression of both sbGHR1 and sbGHR2 was found to be decreased by estradiol treatment in black seabream. This decreased receptor expression in the seabream liver by estradiol in fact provides an explanation to a recent report that estradiol decreases GH-stimulated expression of IGF-I mRNA in the seabream liver (Carnevali et al 2005). In mammals, rather diverse observations on estradiol regulated GHR expression have been reported.…”
Section: Discussionmentioning
confidence: 57%
“…However, even without assuming a causative role of the EE 2 -induced activation and upregulation of the ER pathway, our results suggest that administration of EE 2 during early development exerts a long-term suppressive effect on hepatic IGF-I expression and synthesis. Previous in vivo and in vitro studies in adults of different fish species also reported an estrogen-associated decrease in hepatic IGF-I mRNA (Riley et al 2004, Carnevali et al 2005, Filby et al 2006 or in serum IGF-I (Arsenault et al 2004, McCormick et al 2005.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, there is a rising interest in the significance of IGF-I in fish development, growth, and reproduction. In this respect, some evidence has been presented (Riley et al 2004, Carnevali et al 2005, McCormick et al 2005) that estrogens may acutely influence synthesis and/or release of IGF-I from adult fish liver. Very recently, the influence of exposure to estrogen (E 2 ) on several genes, including IGF-I, has been investigated in adults of the fathead minnow (Filby et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show that teleost fishes including salmonids, sea bream, carp, catfish, eels, rabbitfish, sea bass, and hybrid striped bass, as well as the dogfish, an elasmobranch, differ from mammals in that liver igf2 gene expression and plasma Igf2 levels are stimulated by GH and respond to metabolic status (Shamblott et al 1995, Tse et al 2002, Vong et al 2003a, Peterson et al 2004, Carnevali et al 2005, Gabillard et al 2006, Wilkinson et al 2006, Ayson et al 2007, Terova et al 2007, Gahr et al 2008, Moriyama et al 2008a, b, Picha et al 2008b, Ponce et al 2008, Devlin et al 2009, Peterson & Waldbieser 2009, Eppler et al 2010, Pierce et al 2010. In primary cultured coho salmon hepatocytes, insulin directly increased igf2 mRNA, and strongly increased the response of igf2 mRNA to GH, but suppressed the response of igf1 mRNA to GH (Pierce et al 2005(Pierce et al , 2010.…”
Section: Introductionmentioning
confidence: 99%